Impact Investment for BRICS Cooperation on Sustainable Development - Mujumdar, Anita (Animo Repository, 2021)
A sustainable development agenda has always been at the core of BRICS cooperation. However, the progress has been limited for many reasons, including economic diversity, over-reliance on Western technologies and capital, lack of own sources of financing, and common strategy. At the same time, accounting for over 40% of the global population, over 20% of the world’s GDP, and contributing to more than 40% of global CO2 emissions, BRICS countries are among the world’s most important players in sustainability and climate. Therefore, finding organic ways of sustainable growth in these countries is crucial to global efforts in achieving sustainable development goals (SDGs). Using a qualitative data analysis, a review of the literature and reports of international organizations, this paper aims to analyze the current trends, risks, and opportunities in the advancement of BRICS cooperation on SDGs while placing a special emphasis on impact investment as a way to bring additional finance to BRICS countries.